On the mechanisms that lead to multiple ground contacts in lightning - Leandro Zanella de Souza Campos (2016)
Negative cloud-to-ground (-CG) lightning is an essentially discrete phenomenon (with multiple individual return strokes) and frequently strikes ground on more than one location. The main objective of this thesis work is to bring new light into the mechanisms through which a CG can produce more than one ground termination and which factors modulate that characteristic. The first step towards that goal was the development of an algorithm, named groupGCP, that is capable of processing data provided by VLF/LF Lightning Location Systems (LLS) and deriving ground contact point (GCP) information by grouping each stroke into an optimized strike point position. This is the first method of this kind that makes full use of all error ellipse parameters provided by some of the present day sensor technologies. The second step concerns detailed individual case studies of lightning events. The first of these analyses approaches the phenomenology of forked and upward-illumination strokes. They are capable of touching ground at multiple locations within very short intervals, ranging from a few microseconds up to a few milliseconds. Some crucial differences between these two classes of events are identified and discussed in detail. Next, the more common subsequent new ground contact (NGC) stroke is analyzed from data provided by a three-dimensional VHF Lightning Mapping Array (LMA) along with auxiliary information provided by VLF/LF LLS, video and electric field records. Three very distinct mechanisms that lead to NGC subsequent strokes were identified: Type I consists of dart leaders that diverge from the path of the preceding stroke; Type II originate from in-cloud horizontally propagating channels that move away from the preceding GCP during the interstroke interval; and Type III consists of NGC subsequent strokes that originate as apparently independent stepped leader processes. The sample of events of each class suggests that Type I commonly produce ground terminations up to 1 km away from the preceding GCP, while Types II and III may lead to horizontal separations between GCPs of more than 7 km. In the third step some factors that may modulate the occurrence and characteristics of multi-grounded flashes are analyzed. Spatial distributions are compared with complex terrain features (both absolute altitude and high spatial frequency variations) for three different domains. No consistent correlation was found for all of them and, although some insights could be obtained, further investigations with additional instruments are necessary to evaluate any possible relationship. Also, diurnal climatology of the mean number of channels per flash and the separation between them were obtained. All three domains presented very similar diurnal cycles, suggesting that there may be driving factors or mechanisms that are shared among all of them. However, the possibility that the observed trends are actually caused by classification errors by the algorithm is also discussed. Finally, the thesis concludes with two examples of technological applications of the groupGCP algorithm: the improvement of risk assessment techniques that are suggested by international lightning protection standards, and the analysis of lightning-caused power line faults.